2017
DOI: 10.1136/jnnp-2017-317134
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral inflammation in prodromal Alzheimer’s and Lewy body dementias

Abstract: ObjectivesThere is growing evidence for the role of systemic inflammation in Alzheimer’s disease (AD) and other neurodegenerative diseases; however the systemic inflammatory profile in dementia with Lewy bodies (DLB) has never before been investigated. This study aimed to characterise systemic inflammatory mediators in established DLB and AD, as well as in their prodromal, mild cognitive impairment (MCI) phases.MethodsWe obtained plasma samples from patients with DLB (n=37), AD (n=20), MCI with DLB profile (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
129
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 155 publications
(136 citation statements)
references
References 45 publications
6
129
1
Order By: Relevance
“…As described previously, 17,18,20 four symptoms, and evidence of decline which was a characteristic of AD with no evidence for another aetiology, i.e. they met the additional criterion of 'aetiology of MCI consistent with AD pathophysiologic process').…”
Section: Diagnosismentioning
confidence: 81%
“…As described previously, 17,18,20 four symptoms, and evidence of decline which was a characteristic of AD with no evidence for another aetiology, i.e. they met the additional criterion of 'aetiology of MCI consistent with AD pathophysiologic process').…”
Section: Diagnosismentioning
confidence: 81%
“…It has been shown in previous studies that inflammation occurs early in MCI-AD and MCI-DLB, and inflammation decreases as disease progresses to dementia, 16 suggesting that anti-inflammatory medications may be of use in early stages of disease in these patients. It has been shown in previous studies that inflammation occurs early in MCI-AD and MCI-DLB, and inflammation decreases as disease progresses to dementia, 16 suggesting that anti-inflammatory medications may be of use in early stages of disease in these patients.…”
Section: Discussionmentioning
confidence: 94%
“…16 In the current study, we aimed to investigate this further in patients with PD-MCI. 16 In the current study, we aimed to investigate this further in patients with PD-MCI.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In their  JNNP  paper, King et al 3 present the results of a study investigating peripheral inflammation markers in plasma samples from 37 patients with DLB, 20 patients with AD dementia, 38 patients with mild cognitive impairment (MCI) and DLB profile, 20 patients with MCI and AD profile and 20 normal controls. This study indicated that increased peripheral inflammation occurs at the MCI stages and disappears with disease progression in both DLB and AD.…”
Section: The More Reliably Identifiable Prodromal Phase Of Dementia Wmentioning
confidence: 99%